Antibiotics Profile, Prevalence of Extended-Spectrum Beta-Lactamase (ESBL), and Multidrug-Resistant Enterobacteriaceae from Different Clinical Samples in Khartoum State, Sudan - Ehssan H. Moglad (International Journal of Microbiology)
One of the global requirements for controlling the occurrence of resistance to antimicrobial drugs is to understanding the resistivity profile of various clinical isolates. Therefore, this study aimed to deliver the indication of different resistant profiles of clinically isolated Enterobacteriaceae from different sources of samples from Khartoum state, Sudan, and to determine the prevalence rate of extended-spectrum beta-lactamase (ESBL), multidrug-resistant (MDR), extensively drug-resistant (XDR), and pandrug-resistant (PDR) bacteria. A total of 144 Gram-negative bacteria were collected from different sources (vaginal swab, urine, catheter tip, sputum, blood, tracheal aspirate, pus, stool, pleural fluid, and throat swab). Samples were subcultured and identified according to their cultural characteristics and biochemical tests. Antimicrobial susceptibility test was performed for twenty-four antibiotics from eleven categories against all isolated Enterobacteriaceae according to the recommendation of Clinical and Laboratory Standards Institute (CLSI). The result showed that out of 144 isolates, Escherichia coli and Klebsiella pneumoniae were predominant isolates with the percentage of 47.9 and 25%, respectively. The prevalence of ESBL was higher in K. pneumonia (38.9%) than E. coli (34.8%). All isolated E. coli were sensitive to nitrofurantoin and tigecycline. There was a high prevalence of MDR Enterobacteriaceae, and only one isolate was XDR, while PDR was zero for all isolated bacteria. Active antimicrobial-resistant (AMR) observation through constant data sharing and management of all stakeholders is crucial to recognize and control the AMR global burden. Also, effective antibiotic stewardship procedures would be applied to limit the unreasonable expenditure of antibiotics in Sudan.